Sosialisasi Pembuatan Bakso Ikan Lele Di Desa Air Emas Dalam Program Pengabdian Kepada Masyarakat - Hambali Hambali; Adis Erfiqovina; Baihaqi Hakim; Chusnul Khotimah Arramadani; Herma Liza; Mochamad Rikki Setiawan; Rika Ayu Astriani; Resti Destari; Saputri Kenanga Dewi; Sri Darmayani; Tiwi Fafrelia Aghata (jurnal ABDIMAS Indonesia, 2023)
Air Emas Village is a village born from the transmigration class of 1991, the majority of which the population was imported from Java. The Air Emas Village KKN was carried out from July 10 – August 18, 2023 in Air Emas Village, Singingi District, Kuantan Singingi Regency, Riau, which consisted of 10 students, successfully conducting socialization activities for making fish balls made from catfish. The method carried out is the survey method and goes directly to the field. Consideration of the social and economic conditions of the village makes this activity one of the suitable activities to be carried out in Air Emas Village. The use of catfish raw materials because this fish is rich in protein and also has omega-3. The target of this activity is PKK mothers who will later use it to be a form of MSMEs. The purpose of this activity is to build the foundation of MSMEs to the community and be able to build businesses and form healthy patterns for the people of Air Emas Village.